Structural Survey and Empirical Seismic Vulnerability Assessment of Dwellings in the Historical Centre of Cusco, Peru. Issue 10 (3rd October 2021) - Brando, Giuseppe; Cocco, Giulia; Mazzanti, Claudio; Peruch, Matteo; Spacone, Enrico; Alfaro, Crayla; Sovero, Karim; Tarque, Nicola
ABSTRACT: This paper deals with the seismic vulnerability assessment of dwellings in the historic centre of Cusco (Peru), one of the most important UNESCO sites in the world. This activity is framed within a cooperation agreement between the University of Chieti-Pescara (Italy), the Andina University del Cusco (Peru), the Pontifical Catholic University of Peru and the Cusco Municipality (Peru) whose main focus is the seismic risk evaluation of the whole historic centre. Following a discussion on the development of the historic centre and the main construction typologies, the paper presents the main outcomes of an extensive in-situ survey for collecting structural information on the buildings. Statistics regarding the data are given and shown in a GIS environment. The collected data are then used to implement an empirical model for the seismic vulnerability assessment of a significant part of the historic centre. The model is derived using a methodology already proposed by the authors for Italian historic centres. The original model is adapted to the peculiarities of the structural typologies found in Cusco. Finally, fragility curves are derived and used in order to assess the potential seismic vulnerability reduction achieved by applying proper retrofitting interventions at the large scale.